First Year Pre-Service Teachers’ Self-Perception of Digital and Scientific Literacy: Implication for Course Design - Ramadani, Shefa Dwijayanti; Lestari, Ayu (BIOEDUKASI, 2024)
Teachers in the 21st century are expected to be mastering 21st century skills, so pre-service teachers need to be prepared to become professional teachers starting from the education period while studying at university. Mastery of digital and scientific literacy is considered to be the core of the literacy required in 21st century education. This research is a quantitative study using the survey method. The subject of this research is first year science education students at a university in Magelang, totaling 141 students. Descriptive statistics were employed to investigate the digital and scientific literacy. Based on the results of the study, it can be concluded that pre-service teachers' self-perception of digital and scientific literacy are in the medium category, which means that there is a need to develop effective course designs for promoting both literacies among preservice teachers in order to support the quality of teacher education in Indonesia.